Trade Policy Options of Ukraine: East or West - Irena Mikolajun; Richard Paap; Jean-Marie Viaene; Olga Zelenko (Tinbergen Institute, 2016)
The dissolution of the Soviet Union in 1991 has led to the independence of fifteen new states. Twelve of these, including Ukraine, joined the Commonwealth of Independent States (CIS) whose goal was to form a common economic space with free movement of goods, labor and capital. Twenty five years later, CIS countries still face important trade policy choices, the implementation of which is conditional on the quality of governance and infrastructure. The evaluation of these policy choices gains therefore considerable importance. Using an unbalanced panel data set of bilateral export flows among 159 economies, we estimate the gravity model of trade using alternative estimation approaches that account for zeros in trade: Heckman, Poisson pseudo-maximum likelihood and Martin-Pham Tobit. Our empirical results show robust outcomes and advocate importance of WTO membership, governance and effective distance (corrected for infrastructure). Using scenario analyses we assess counterfactuals for Ukraine and find, for example, that improved infrastructure would on average lead to a 22% increase in Ukrainian exports while improved governance would, ceteris paribus, almost double its trade. Most of these changes originate from the intensive margin of trade.
Keywords: C23; F13; F14; F17; F31; F33; O43; 330; extensive/intensive margins; governance; gravity model; infrastructure; regional trade agreements; zero trade